Isolated third cranial nerve palsy as the first presentation of multiple myeloma. Issue 3 (24th March 2021) - Vaid, Tejasvini; Dhawan, Rishi; Aggarwal, Mukul; Tyagi, Seema
Abstract : A 50-year-old woman presented with a right-sided isolated third cranial nerve palsy. MRI brain showed a mass lesion arising from the right clivus with extension into the cavernous sinus. Blood investigations and bone marrow biopsy were suggestive of multiple myeloma with hypercalcaemia and renal dysfunction. It was unclear at first if the intracranial lesion was due to myelomatous involvement or a separate disease entirely. The patient declined consent for a biopsy and cerebrospinal fluid analysis was inconclusive. She was treated with bortezomib based chemotherapy and the palsy resolved by day 6, which helped clinch the rare diagnosis of central nervous system (CNS) involvement by multiple myeloma. Most patients with CNS myeloma have a dismal survival of under 6 months but she is on therapy for relapse 26 months after diagnosis. While placed under the umbrella of CNS myeloma, patients with osteodural myeloma have better outcomes, perhaps due to their distinct aetiopathogenesis.